Measurement of the WW+WZ cross section and limits on anomalous triple gauge couplings using final states with one lepton, missing transverse momentum, and two jets with the ATLAS detector at s√=7 TeV - Onofre, A. (2015)
The production of a W boson decaying to eν or μν in association with a W or Z boson decaying to two jets is studied using 4.6 fb−1 of proton--proton collision data at s√=7 TeV recorded with the ATLAS detector at the LHC. The combined WW+WZ cross section is measured with a significance of 3.4σ and is found to be 68±7 (stat.)±19 (syst.) pb, in agreement with the Standard Model expectation of 61.1±2.2 pb. The distribution of the transverse momentum of the dijet system is used to set limits on anomalous contributions to the triple gauge coupling vertices and on parameters of an effective-field-theory model.